Analisis Kebutuhan Keterampilan Berbahasa Jepang di Bidang Perhotelan: Studi Kasus Mahasiswa Prodi Manajemen Perhotelan - Rahmalina, Reny; Syihabuddin, Syihabuddin; Gunawan, Wawan; Arianingsih, Anisa (Journal of Indonesian Tourism, Hospitality and Recreation, 2023)
ABSTRACTThe purpose this research is to investigate the interns of the Hospitality Management study program at Padang State University in terms of their needs and problems in using Japanese language skills namely listening, speaking, reading, and writing related to their work during their internships in various hotels before graduating. The participants were 60 intern students and three supervisors who worked in various hotels. Data collection was carried out through questionnaires and interviews. The findings reveal that most of the intern students who work in hotels evaluate their Japanese language skills at a moderate level. Students feel the need to improve their Japanese language skills. Of the four Japanese skills, listening and speaking are the most problematic. Meanwhile, between writing and reading abilities, students feel competent in reading skills rather than writing. The results showed that students' Japanese language skills did not increase, especially in writing and speaking skills which would have an impact on the quality of performance and impact on the excellent service provided to hotel guests. Therefore, there is a need for cooperation from various parties to make this happen.ABSTRAKTujuan penelitian ini untuk menginvestigasi mahasiswa magang program studi Manajeman Perhotelan di Universitas Negeri Padang dalam hal kebutuhan dan masalah mereka dalam menggunakan keterampilan bahasa Jepang yakni mendengarkan, berbicara, membaca, dan menulis terkait dengan pekerjaan mereka selama magang di berbagai hotel sebelum lulus. Partisipannya 60 mahasiswa magang dan tiga orang supervisor yang bekerja di berbagai hotel. Pengumpulan data melalui kuesioner dan wawancara. Sebagian besar mahasiswa magang yang bekerja di hotel mengevaluasi diri terhadap kemampuan bahasa Jepang yakni di tingkat sedang. Mahasiswa perlu meningkatkan kemampuan bahasa Jepang. Dari keempat kemampuan berbahasa Jepang, kemampuan mendengarkan dan berbicara yang paling bermasalah. Sedangkan antara kemampuan menulis dan membaca, mahasiswa merasa berkemampuan dalam membaca daripada menulis. Hasil penelitian menunjukkan bahwa kemampuan keterampilan bahasa Jepang mahasiswa tidak meningkat, khususnya pada keterampilan menulis dan berbicara akan berakibat pada kualitas kinerja dan berdampak pada pelayanan prima yang diberikan pada tamu hotel. Oleh karena itu, perlu adanya kerjasama dari berbagai pihak untuk mewujudkan hal ini.